2009
DOI: 10.1371/journal.pgen.1000618
|View full text |Cite
|
Sign up to set email alerts
|

The Genome of Nectria haematococca: Contribution of Supernumerary Chromosomes to Gene Expansion

Abstract: The ascomycetous fungus Nectria haematococca, (asexual name Fusarium solani), is a member of a group of >50 species known as the “Fusarium solani species complex”. Members of this complex have diverse biological properties including the ability to cause disease on >100 genera of plants and opportunistic infections in humans. The current research analyzed the most extensively studied member of this complex, N. haematococca mating population VI (MPVI). Several genes controlling the ability of individual isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
322
2
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 411 publications
(349 citation statements)
references
References 95 publications
7
322
2
4
Order By: Relevance
“…Unlike previous observations in a number of fungal plant pathogens, including F. oxysporum, N. haematococca, and Z. tritici, which display karyotype variation as a consequence of the differential presence of small dispensable chromosomes (Coleman et al 2009;Ma et al 2010;Stukenbrock et al 2010;Goodwin et al 2011;Raffaele and Kamoun 2012), the karyotype variation that we observed between individual isolates of V. dahliae concerns chromosome length polymorphisms, and no indication for the occurrence of small dispensable chromosomes is found in V. dahliae. The observed variation in this study and previous ones among fungal karyotypes (Zolan 1995) is the result of complex chromosomal rearrangements.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike previous observations in a number of fungal plant pathogens, including F. oxysporum, N. haematococca, and Z. tritici, which display karyotype variation as a consequence of the differential presence of small dispensable chromosomes (Coleman et al 2009;Ma et al 2010;Stukenbrock et al 2010;Goodwin et al 2011;Raffaele and Kamoun 2012), the karyotype variation that we observed between individual isolates of V. dahliae concerns chromosome length polymorphisms, and no indication for the occurrence of small dispensable chromosomes is found in V. dahliae. The observed variation in this study and previous ones among fungal karyotypes (Zolan 1995) is the result of complex chromosomal rearrangements.…”
Section: Discussioncontrasting
confidence: 99%
“…Various mechanisms have been described that facilitate rapid development of novel effector genes in pathogenic microbes, including diversity at genomic locations enriched for transposons, mutation, and recombination in subtelomeric regions (McDonagh et al 2008;Chuma et al 2011), coregulated gene clusters (Pallmer and Keller 2010;Schirawski et al 2010), small dispensable chromosomes (Coleman et al 2009;Ma et al 2010;Stukenbrock et al 2010;Goodwin et al 2011;Raffaele and Kamoun 2012), gene sparse regions (Raffaele et al 2010), ATrich isochore-like regions (van der Wouw et al 2010; Rouxel et al 2011), genome hybridization , and horizontal gene transfer (Friesen et al 2006;de Jonge et al 2012;Gardiner et al 2012). However, most of these mechanisms have been described in species that can reproduce sexually, and of which the genomes were shaped by repeat-driven expansion (Raffaele and Kamoun 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The centromeres of filamentous fungi have been difficult to assemble and are absent or not easily recognizable by bioinformatic tools in the almost completely sequenced and assembled genomes of Fusarium graminearum (teleomorph: Gibberella zeae) (20), Aspergillus fumigatus (26), Nectria haematococca (18), and even the one filamentous fungus for which there is a predicted "telomere-to-telomere" assembly, Mycosphaerella graminicola (http://genome.jgi-psf.org/Mycgr3/Mycgr3.info.html).…”
mentioning
confidence: 99%
“…Host adaptation and host switching is often reflected in encoded effector protein composition. Between closely related taxa of Nectria haematococca and Fusarium oxysporum this adaptation is achieved by proteins encoded on 12 MUSZEWSKA A. supernumerary chromosomes carrying, among others, host specific effectors and mobile elements (Coleman et al 2009, Ma et al 2010 (Raffaele & Kamoun 2012). In the genome of Pyrenophora tritici-repentis TEs mediated adaptation towards pathogenicity by contributing to novel gene creation, effector diversification, facilitating horizontal gene transfer events and transduplication (Manning et al 2013).…”
Section: Effector Proteinsmentioning
confidence: 99%